THE IMPACTS OF BONDING ON THE LIFE OF THE TWO WOMEN IN G.D. JOHNSON’S FREE - Ratna Asmarani (Institut Seni Indonesia Yogyakarta, 2020)
Abstract: The aim of this paper is to discuss the unique relationship between two women living in the same roof for 25 years which takes an unexpected turn after the breadwinner that unites them uncompromisingly passes away. The focus is on the impacts of the changing types of bonding on the life of the two women in G.D. Johnson’s short story entitled Free. To support the discussion, several concepts are borrowed, such as the concepts of female domesticity and patriarchy. Since the center of analysis is on the women, the feminist criticism is used. This criticism is supported by contextual method of literary analysis which combines the extrinsic elements with the intrinsic ones especially character, conflict, and setting. The result shows that the death of the patriarchal figure breaks the imposing bonding in the life of the two women. After a moment of internal conflict experienced by each woman, both can put aside their uncomfortable past to create a mutual bonding for the rest of their life. Key words: female domesticity, patriarchy, contextual method